Contribution to the knowledge of ptyctimous mites (Acari, Oribatida) in the Palm House in Poznań - Niedbała, Wojciech (Biological Letters, 2011)
In soil samples from the Palm House (Palmiarnia) in Poznań city, six alien and six native mite species of the ptyctimous were found. Nearly half of them are semicosmopolitan but two of them are not native to Europe. One of the species, Phthiracarus phoxos Niedbała 2004, is endemic to Cuba. Supposedly the wellbeing of the exotic fauna depends on the presence of exotic soil and careful addition of native soil.